INDONESIA'S ENERGY SECURITY: ARE WE SECURING IT RIGHT? LESSON LEARNED FROM THE EU - Dwiesta, Afghania (UI Scholars Hub, 2017)
Over the past few years, one of Indonesia’s state-owned enterprises, PLN, has conducted dialogues focusing on developing a new value-creative business model to transform itself, a sleepy regulated utility, into a truly competitive electricity service provider. However, efforts to preserve the prominence of the Country’s electricity sector have been ongoing as the sector is still experiencing sustained rolling blackouts, net import dependency and lack of transmission facility enforcement throughout the Indonesian archipelago. Such efforts have been varied from the incentivise policy and programs such as the Public-Private Partnership and the two phases of Fast Track Program. The reformation of electricity law dated back on the 1985, 2002 and 2009 to attract investors in the development of Indonesia’s electricity sector have been enacted, but a controversial issue arose from the annulment of the Law No. 20 Year 2002 on Electricity by the Constitutional Court Decision No. 001- 021-022/PUU-I/2003 stating that such law which clearly stating that the requirement to privatise electricity operation was unconstitutional. This article will try to provide a comprehensive comparative analysis of such decision with the common practice adopted by the EU which has successfully implemented its deregulation and separation of the electricity’s business chain through unbundling the sector as part of liberalisation.